Marketing of Financial Service: Evidence from Nigeria Financial Market - Lucky, Lucky Anyike (International Journal of Marketing Research Innovation, 2018)
Nigeria financial market is emerging, the growth in institutions and products require a marketing strategy that will meet the needs of growing population. This study examined marketing of financial services. It discussed financial service products, segmentation of financial products, brands in financial market, financial service marketing environment, marketing of financial service through the internet, distribution channels of financial products, strength, weakness, opportunities and threat of Nigeria financial market, the needs for marketing of financial services, features of financial products and pricing of financial products. The study concludes that marketing of financial services is a determinant of financial inclusion, therefore policies and strategies should be advanced by management and regulators in the financial market.